1993
DOI: 10.1002/ddr.430290305
|View full text |Cite
|
Sign up to set email alerts
|

Effect of calcium binding protein modulators on myofibrillar MgATPase activity and cGMP‐inhibitable phosphodiesterase activity from human cardiac muscle

Abstract: Cardiac muscle force development and shortening result from the interaction between actin and myosin within the myofibrillar contractile unit. This interaction is dependent upon intracellular Ca2+ and i s controlled by the troponin-tropomyosin regulatory proteins situated along the length of the actin thin filament. Enhancing the Ca2+ sensitivity of cardiac contractile protein interactions has been proposed as a novel mechanism for some positive inotropic agents. These myofibrillar Ca2+ sensitizers have variab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

1994
1994
2012
2012

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 28 publications
0
5
0
Order By: Relevance
“…Furthermore, patients with reduced ventricular function were more sensitive to these effects when compared with patients with normal ventricular function . However, other data suggested that pimobendan's inotropic effect on the failing human myocardium was predominantly due to inhibition of PDE3 . Studies have also evaluated the mechanism of action of pimobendan's active metabolite.…”
Section: Preclinical Investigationsmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, patients with reduced ventricular function were more sensitive to these effects when compared with patients with normal ventricular function . However, other data suggested that pimobendan's inotropic effect on the failing human myocardium was predominantly due to inhibition of PDE3 . Studies have also evaluated the mechanism of action of pimobendan's active metabolite.…”
Section: Preclinical Investigationsmentioning
confidence: 99%
“…17 However, other data suggested that pimobendan's inotropic effect on the failing human myocardium was predominantly due to inhibition of PDE3. 68 Studies have also evaluated the mechanism of action of pimobendan's active metabolite. The PDE3 inhibitory action of UD-CG 212 Cl was significantly more potent than that of pimobendan.…”
Section: Preclinical Investigationsmentioning
confidence: 99%
“…Most drugs affect the enzyme indirectly, via enhanced calcium binding to the myofibrils, most probably to troponin-C. As enhanced calcium binding can only be interpreted in terms of more troponin-C molecules binding calcium to their regulatory site, it is obvious that more myosin heads will be recruited to generate crossbridges, resulting in an equivalent increase in myosin ATPase activity. This scenario has been reported for most drugs described above (29,58,70,82,103,124), with the exception of levosimendan (38).…”
Section: Mechanisms Of Myofilament Calcium Sensitizationmentioning
confidence: 79%
“…In fact, compounds developed in the early 1980s were predominantly phosphodiesterase-111 inhibitors, and showed only modest calciumsensitizing activity at much higher doses ( Table 1). Although most investigators interpreted their results generally as calcium sensitization at least being involved in the particular drug's positive inotropic effect, the relevance of sensitization at much higher concentrations has been questioned (82). More recently developed compounds have been reported to have predominantly calcium-sensitizing activity.…”
Section: Medicinal Chemistry and Pharmacology Of Calcium Sensitizersmentioning
confidence: 99%
See 1 more Smart Citation